Lichenoid and Granulomatous Stomatitis Diagnosis and Treatment: Report of Three Cases - Bakhshi, Mahin; Bagheri, Leyla; Dalirani, Sara; Bigom Taheri, Jamileh; Mashhadi Abbas, Fatemeh; Atarbashi Moghadam, Saede; Ladan Moghaddam, Mahsa (Journal of Dental School, 2025)
Objective(s): Lichenoid and granulomatous stomatitis (LGS) is a rare inflammatory condition of the oral mucosa that clinically mimics oral lichen planus, posing diagnostic and therapeutic challenges. Case: This report described three cases of LGS in adults aged 55–63, each presenting with persistent burning sensations and chronic ulcers of the upper labial mucosa. Histopathologic evaluation in all cases revealed features consistent with lichenoid and granulomatous inflammation. Despite initial misdiagnosis and ineffective corticosteroid treatment, all patients showed marked improvement with chlorhexidine mouthwash. Conclusion: Accurate diagnosis of LGS is essential due to its resistance to standard corticosteroid therapies commonly used for similar lesions. Chlorhexidine may be an effective alternative, and early histopathological confirmation is recommended for proper management.